Mathematical modeling of soil and water losses in Oxisol under management systems (Research, Society and Development, 2021)
The objective of this work was to mathematically model the losses of water and soil in a Oxisol with different management systems, through the physical attributes of soil and vegetation cover. The experimental area was located in the municipality of Santa Tereza do Oeste – PR, in a soybean field. The treatments consisted of three management systems: traditional no-tillage system, plastered no-tillage system, no-tillage system with scarification and twelve treatments of no-tillage system with cover species in intercropping or not, called “recoverers” of soil structure. Data on water and soil losses were collected at each precipitation in the collector gutters installed in each treatment throughout the soybean cycle. The design was completely randomized. The Statistica software was used to adjust the curve of water and soil losses and submodels were generated to estimate straw and green cover values along the soybean cycle. In general, the highest losses are related to higher density and lower soil macroporosity, while the relationship between straw dry mass and green cover was inversely proportional. The use of part-defined function to mathematically model was adequate to estimate green cover values along the soybean cycle.